International fragmentation : boon or bane for domestic employment? - Hartmut Egger; Udo Kreickemeier (Center for Economic Studies and ifo Institute (CESifo), 2005)
In this paper, we introduce the fairness approach to efficiency wages into a standard model of international fragmentation. This gives us a theoretical framework in which wage inequality and unemployment rates are co-determined and therefore the public concern can be addressed that international fragmentation and outsourcing to low wage countries lead to domestic joblosses. We develop a novel diagrammatic tool to illustrate the main labour market effects of international fragmentation. We also explore how preferences for fair wages and the size of unemployment benefits govern the employment effects of outsourcing and critically assess the role of political intervention that aims to reduce unemployment benefits under internationally fragmented production.
Keywords: F16; F11; 330; international fragmentation; unemployment; fair wages; Outsourcing; Internationale Arbeitsteilung; Beschäftigungseffekt; Auslandsproduktion; Arbeitsmarkt; Effizienzlohn; Lohnstruktur; Globalisierung; Theorie